2021
DOI: 10.3390/antibiotics10040363
|View full text |Cite
|
Sign up to set email alerts
|

Indole Derivatives Obtained from Egyptian Enterobacter sp. Soil Isolates Exhibit Antivirulence Activities against Uropathogenic Proteus mirabilis

Abstract: Proteus mirabilis is a frequent cause of catheter associated urinary tract infections (CAUTIs). Several virulence factors contribute to its pathogenesis, but swarming motility, biofilm formation, and urease activity are considered the hallmarks. The increased prevalence in antibiotic resistance among uropathogens is alarming and requires searching for new treatment alternatives. With this in mind, our study aims to investigate antivirulence activity of indole derivatives against multidrug resistant P. mirabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 46 publications
2
14
0
Order By: Relevance
“…These results provoked the question, what advantage would staquorsin have over the already described QS inhibitor, savirin. A key feature sought in anti-virulence therapies is their lack of negative impact on the viability of the pathogen, leading to a decrease in the frequency of resistance development ( Rasko and Sperandio, 2010 ; Heras et al, 2015 ; Rampioni et al, 2017 ; Totsika, 2017 ; Fleitas Martinez et al, 2019 ; Amer et al, 2021 ). In the work described by Sully and co-workers, they showed that savirin has no effect on the viability of S. aureus in a concentration up to 6.3 μM, however, upon testing the anti-Agr activity of this compound they routinely used a concentration of 5 μg/ml (13.6 μM) which is more than double the concentration indicated to have no effect on the viability ( Sully et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results provoked the question, what advantage would staquorsin have over the already described QS inhibitor, savirin. A key feature sought in anti-virulence therapies is their lack of negative impact on the viability of the pathogen, leading to a decrease in the frequency of resistance development ( Rasko and Sperandio, 2010 ; Heras et al, 2015 ; Rampioni et al, 2017 ; Totsika, 2017 ; Fleitas Martinez et al, 2019 ; Amer et al, 2021 ). In the work described by Sully and co-workers, they showed that savirin has no effect on the viability of S. aureus in a concentration up to 6.3 μM, however, upon testing the anti-Agr activity of this compound they routinely used a concentration of 5 μg/ml (13.6 μM) which is more than double the concentration indicated to have no effect on the viability ( Sully et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The " * " indicates a p-value ≤ 0.05, and " * * * " p-value ≤ 0.001. (Rasko and Sperandio, 2010;Heras et al, 2015;Rampioni et al, 2017;Totsika, 2017;Fleitas Martinez et al, 2019;Amer et al, 2021). In the work described by Sully and co-workers, they showed that savirin has no effect on the viability of S. aureus in a concentration up to 6.3 µM, however, upon testing the anti-Agr activity of this compound they routinely used a concentration of 5 µg/ml (13.6 µM) which is more than double the concentration indicated to have no effect on the viability (Sully et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The antibiofilm activity of the crude indole extract was tested against strong biofilm forming P. mirabilis isolate P8 (Amer et al, 2021), in addition to the standard strain ATCC 12453. Isolate P8 was recovered from the urine sample of a patient suffering from UTI after obtaining the participant's consent and the approval of the Research Ethics Committee-MSA University.…”
Section: Bacterial Cultures and Indole Derivativesmentioning
confidence: 99%
“…Crude indole extract was prepared from a rhizobacterium Enterobacter sp. and coded as Zch127, followed by the identification of composing indole derivatives using LC-MS and HPLC analysis as described in our previous study (Amer et al, 2021). The extract analysis revealed the presence of 9 compounds including tryptophan, 3 methyl indole (skatole), indole-3-carboxylic acid, indole-3-acetic acid, indole-3-lactic acid, indole-3 ethanol, indole-3-pyruvic acid, indole-3 acetaldehyde, indole-3-acetonitrile, indole-3 acetamide.…”
Section: Bacterial Cultures and Indole Derivativesmentioning
confidence: 99%
See 1 more Smart Citation